Does fasting plasma glucose values 5.1-5.6 mmol/l in the first trimester of gestation a matter? - Ramezani Tehrani, Fahimeh; Farzadfar, Farshad; Hosseinpanah, Farhad; Rahmati, Maryam; Firouzi, Faegheh; Abedini, Mehrandokht; Hadaegh, Farzad; Valizadeh, Majid; Torkestani, Farahnaz; Khalili, Davood; Solaymani-Dodaran, Masoud; Bidhendi-Yarandi, Razieh; et al. (Frontiers in Endocrinology, 2023)
Objectives: The aim of the study was to investigate the effect of treatment on pregnancy outcomes among women who had fasting plasma glucose (FPG) 5.1-5.6 mmol/l in the first trimester of pregnancy. Methods: We performed a secondary analysis of a randomized community non-inferiority trial of gestational diabetes mellitus (GDM) screening. All pregnant women with FPG values range 5.1-5.6 mmol/l in the first trimester of gestation were included in the present study (n=3297) and classified as two groups: They were labeled as (i) GDM who received treatment for GDM (n=1,198), (ii) non-GDM who received usual-prenatal-care (n=2,099). Macrosomia/large for gestational age (LGA) and primary cesarean section (C-S) were considered as primary outcomes. A modified-Poisson-regression for binary outcome data with a log link function and robust error variance was used to RR (95%CI) for the associations between GDM status and incidence of pregnancy outcomes. Results: The mean maternal age and BMI of pregnant women in both study groups were similar. There were no statistically significant differences in the adjusted risks of adverse pregnancy outcomes, including macrosomia, primary C-S, preterm birth, hyperbilirubinemia, preeclampsia, NICU admission, birth trauma, and LBW among those women, with FPG values range 5.1-5.6 mmol/l in the first trimester of gestation been labeled as GDM with non-GDM ones. Conclusions: It is found that treating women with first-trimester FPG values of 5.1-5.6 mmol/l could not improve adverse pregnancy outcomes. Therefore, extrapolating the FPG cut-off point of the second trimester to the first –which has been proposed by the IADPSG, might therefore not be appropriate.